2020
DOI: 10.2147/cmar.s264070
|View full text |Cite
|
Sign up to set email alerts
|

<p>Ursolic Acid Protects Against Proliferation and Inflammatory Response in LPS-Treated Gastric Tumour Model and Cells by Inhibiting NLRP3 Inflammasome Activation</p>

Abstract: Background Inflammation is considered as one of the hallmarks of cancer development and progression. Ursolic acid (UA) showed strong effects as an anti-inflammatory and antioxidant. However, the anti-cancer effects of ursolic acid require further study. Methods This study aimed to investigate the role of ursolic acid in a lipopolysaccharide (LPS)-treated gastric tumour mouse model and in a human gastric carcinoma cell line (BGC-823 cells). This study also aimed to confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Several studies have reported that the activation of the NLRP3/Caspase-1 pathway is associated with tumor progression (24)(25)(26)(27). Wang et al (25) found that when the NLRP3 inflammasome is activated, Caspase-1 is spliced to further activate the Akt, GSK-3p, ERK1/2 and CREB signaling pathways to promote tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that the activation of the NLRP3/Caspase-1 pathway is associated with tumor progression (24)(25)(26)(27). Wang et al (25) found that when the NLRP3 inflammasome is activated, Caspase-1 is spliced to further activate the Akt, GSK-3p, ERK1/2 and CREB signaling pathways to promote tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological levels of NLRP3 activation protects the body's inflammatory immune system via activation of Caspase-1, whereas uncontrolled activation will lead to dysregulated inflammation, autoimmune diseases, neurodegenerative diseases, and even malignant tumors (20)(21)(22)(23)(24). Recently, a number of studies have reported that the overactivation of NLRP3 is closely associated with the progression of several malignant tumors (24)(25)(26)(27). To date, there are numerous studies on the downstream effects of NLRP3 (22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…The 5-FU treatment using a therapy relevant dosing 5 mg/kg, 31 where UA was treated in an toxicological acceptable dose 20 mg/ kg. 32 We found that UA exerted extraordinary efficacy (TSI = ~90%) compared to 5-FU (TSI = ~40%). The tumor weight and tumor weight/body weight (TW/BW) ratio were significantly reduced in the UA-treated mice compared to the placebo-treated mice and 5-FU-treated mice (Figure 4C).…”
Section: Potential Use Of Ua a Novel Aromatase Silencer For Gca Patientsmentioning
confidence: 66%
“…Moreover, we compared the tumor suppression efficacy of 5‐FU and UA (Figure 4A,B) and evaluated their systemic toxicity (Figure 4C) in MKN45 cells xenografted to create a GCa in vivo model. The 5‐FU treatment using a therapy relevant dosing 5 mg/kg, 31 where UA was treated in an toxicological acceptable dose 20 mg/kg 32 . We found that UA exerted extraordinary efficacy (TSI = ~90%) compared to 5‐FU (TSI = ~40%).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation